ADAMTS-1 inhibits angiogenesis via the PI3K/Akt-eNOS-VEGF pathway in lung cancer cells - Wang, Bu; Chen, Shuo; Zhao, Jian-Qing; Xiang, Bao-Li; Gu, Xin; Zou, Fang; Zhang, Zhi-Hua (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Background: ADAMTS-1 (a disintegrin and metalloproteinase with thrombospondin repeats-1) is a recently characterized protein containing a metalloproteinase domain, a disintegrin-like domain and a thrombospondin type 1 motif, which is involved in angiogenesis. However, the roles of ADAMTS-1 in angiogenesis of lung cancer (LC) remain unclear. Methods: The mRNA expression of ADAMTS-1 and VEGF was examined by qRT-PCR. Western blots were used to detect the protein expression of ADAMTS-1 and vascular endothelial growth factor (VEGF) in A549 cells and to analyse the cellular effect of a PI3K/Akt activator and an endothelial nitric oxide synthase (eNOS) activator. ADAMTS-1 and VEGF contents in cell culture supernatants were measured by ELISA. Cell viability, cell cycle, migration, and angiogenesis of HUVECs were evaluated by MTT assay, flow cytometry, scratch assay and tube formation assay, respectively. Results: Our data revealed that the expression of ADAMTS-1 was downregulated, while the expression of VEGF was upregulated in A549 cells. Decreased ADAMTS-1 content was also detected in A549 cell culture supernatant. Overexpression of ADAMTS-1 inhibited VEGF expression and A549 cell proliferation. Moreover, ADAMTS-1 overexpression repressed proliferation, migration and angiogenesis of HUVECs. Mechanistically, ADAMTS-1 suppressed the expression of VEGF in HUVECs by inhibiting PI3K/Akt- eNOS, while a PI3K activator and an eNOS activator each partly reversed the expression of VEGF. In addition, activation of the PI3K/Akt pathway or VEGF overexpression reversed the inhibitory effect of ADAMTS-1 overexpression on HUVECs angiogenesis. Conclusions: These results indicated that ADAMTS-1 inhibited angiogenesis of LC cells via regulation of the PI3K/Akt-eNOS/VEGF axis, which shed light on LC pathogenesis and provided potential targets for LC therapy.